2018
DOI: 10.3389/fnins.2018.00241
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm Shift to Neuroimmunomodulation for Translational Neuroprotection in Stroke

Abstract: The treatment of acute ischemic stroke is still an unresolved clinical problem since the only approved therapeutic intervention relies on early blood flow restoration through pharmacological thrombolysis, mechanical thrombus removal, or a combination of both strategies. Due to their numerous complications and to the narrow time-window for the intervention, only a minority of stroke patients can actually benefit from revascularization procedures, highlighting the urgent need of identifying novel strategies to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 112 publications
0
18
0
Order By: Relevance
“…Morphological changes, occurring during the activation of microglia and astrocytes, or higher proliferation of NG2 glia, microglia and astrocytes are all hallmarks of ischemia (Davalos et al, 2005;Pforte et al, 2005;Burns et al, 2009;Anderova et al, 2011). Another set of pathogenic events, the aforementioned ischemic pathway (Figure 1), takes place in the nervous tissue affected by ischemia (Amantea et al, 2018). Such a series of biochemical processes is a typical consequence of cardiac arrest or stroke.…”
Section: Ischemic Pathwaymentioning
confidence: 99%
“…Morphological changes, occurring during the activation of microglia and astrocytes, or higher proliferation of NG2 glia, microglia and astrocytes are all hallmarks of ischemia (Davalos et al, 2005;Pforte et al, 2005;Burns et al, 2009;Anderova et al, 2011). Another set of pathogenic events, the aforementioned ischemic pathway (Figure 1), takes place in the nervous tissue affected by ischemia (Amantea et al, 2018). Such a series of biochemical processes is a typical consequence of cardiac arrest or stroke.…”
Section: Ischemic Pathwaymentioning
confidence: 99%
“…Cerebral ischaemia ignites a complex, destructive cascade (Figure ) (Amantea, Greco, Micieli, & Bagetta, ; Davis & Pennypacker, ). Interruption of substrate and O 2 delivery stifles ATP production, causing Gibbs free energy of ATP hydrolysis (Δ G ATP ), the thermodynamic driving force for electrolyte transport and other critical cellular processes, to collapse.…”
Section: Adaptation To Intermittent Hypoxia: Robust Cerebroprotectionmentioning
confidence: 99%
“…In contrast, M2 microglia produce anti‐inflammatory cytokines, VEGF, BDNF, platelet‐derived growth factor and progranulin, which collectively suppress inflammation and promote axonal outgrowth, angiogenesis, oligodendrogenesis and remyelination (Hanisch & Kettenmann, ; Kanazawa et al., ; Lo, ). M2 microglia are the more numerous during the first 2 days after stroke; later, M1 microglia predominate (Amantea et al., ). Preventing this M2‐to‐M1 phenotypic shift may promote recovery from stroke (Wang et al., ).…”
Section: Adaptation To Intermittent Hypoxia: Robust Cerebroprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that Toll-like receptor (TLR)-mediated innate immune and inflammatory responses contribute to cerebral I/R injury [4,5]. TLR-mediated signaling pathways predominately activate NF-κB, which is a critical transcription factor that regulates the expression of genes involved in innate and inflammatory responses [6]. Consequently, TLRs may be important targets for the development of new treatment approaches for cerebral I/R injury [7].…”
Section: Introductionmentioning
confidence: 99%